Homologous recombination deficiency (HRD) tests for ovarian cancer: a multicenter French phase II study (HERO) - Raphaël Leman; François Cherifi; Marianne Leheurteur; Pierrick Theret; Camille Pasquesoone; Mathilde Saint-Ghislain; Lucie Bresson; Christophe Denoyelle; Nicolas Vigneron; Laurent Poulain; Raphaël Delepee; Benoit Berby; et al. (BMC Cancer)
Abstract Background The identification of homologous recombination deficient (HRD) tumor is now a crucial step for the therapeutic management of ovarian cancer. The HRD tumors are both sensitive to olaparib maintenance treatment and to platinum-based chemotherapy. Despite the large amount of HRD tests currently available, only a few HRD tests were prospectively validated on a clinical cohort of patients with ovarian cancer. To fulfil these challenges, our laboratory has recently developed a HRD test named GIScar (Genomic Instability Scar). Our HRD test was successfully validated on the retrospective cohort of PAOLA-1 clinical trial regarding the prediction of tumor sensitivity to olaparib. However, we have not yet validated GIScar on a prospective clinical cohort. Methods The HERO trial is a nonrandomized multicenter phase II study aiming to prospectively validate the GIScar test among patients with newly diagnosed high-grade serous ovarian cancer (HGSOC). The primary endpoint is the rate of platinum-sensitive patients (sensitivity after first line of chemotherapy). Platinum-sensitivity is defined as patients without absence of disease progression, according to RECIST 1.1 criteria, six months after a first-line platinum-based chemotherapy) according to GIScar HRD status. Secondary endpoints include the comparison of GIScar and MyChoice CDx (provided by Myriad Genetics®) tests, the assessment of survival according to the HRD status, and the measure of CA-125 concentration kinetic (KELIM). For eligible enrolled patients, two HRD tests will be performed: the GIScar test, and the MyChoice CDx test. Patients will receive a first-line platinum-based chemotherapy, with or without bevacizumab, as per routine practice. A maintenance treatment with olaparib, a PARP inhibitor, will be indicated according to current recommendations for patients with at least one positive HRD test. We plan to enroll 88 patients overall. Patients will be followed up to 48 months after inclusion. Discussion Use of next-generation sequencing (NGS) to identify clinically actionable genomic targets has been incorporated into routine clinical practice in the management of advanced solid tumors and in particular ovarian cancer. Developing new assays is part of the missions of the molecular genetics platforms to improve accessibility and reduce cost compared to non-academic assays. Trial registration IDRCB 2023A0158540, ClinicalTrials.gov NCT06152731 (November 22, 2023). Protocol version Version 3.1 dated from 2024-10-23.